A Tracer Study Survey of Graduates from Balkumari College - Chhetri, Guna Raj; Sedai, Shyam (Journal of Balkumari College, 2019)
This study traced the graduates of Balkumari College of 2017. Descriptive survey method was used to trace their status of employment, with the use of questionnaires. Data were analyzed of simple percentages for significance of relationship. Illuminating were extrapolated and numbered. It aimed to: ascertain the profile of graduates; determine a relationship between their present occupation and the course they finished; and identify the cooperating industries/ institution that employed graduates. Balkumari graduates were proven to proficient and competent to be employable in the schools, banks, IT industries, business industries as revealed in the illuminating themes, thus resulted in boon opportunities. Balkumari mandate, as cascaded in its vision-mission, prepared graduates for the field of work, with personality that matters compared than other predetermined factors. Academic preparation and career performance exhibited signification of successful employment.